Transformation of environmental management: the model of source-based waste management policy implementation in Bali, Indonesia - I Made Sumada; Nyoman Sumawidyani; I Kadek Dede Junaedy; Dewa Putra Sedana; Tunggul Sihombing (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
increasingly serious challenge for tourism destinations, including Bali. The Bali Provincial Government responded through Governor Regulation No. 47 of 2019 concerning source-based waste management, which emphasizes the importance of waste reduction starting from households. This study aims to analyze the implementation model of the policy with a focus on Taro Village, Gianyar Regency, as one of the villages that received funding support for optimizing the management of the Reduce, Reuse, Recycle Waste Processing Site (3R WPS). The theoretical approach used is the Policy Implementation Theory, combining top-down and bottom-up perspectives. The research method used is descriptive qualitative through in-depth interviews, field observations, and document studies. The results of the study indicate that the success of policy implementation is greatly influenced by the role of local actors, community participation, institutional capacity, and budget and technology support. Taro Village faces challenges in terms of community awareness and operational capacity but shows significant local initiatives in source-based waste management. This study contributes to the development of a model for implementing local community-based environmental policies in tourism areas.